PENGARUH PENERAPAN PELAKSANAAN GOOD GOVERNANCE MENURUT UNDANG-UNDANG (UU) NO 6 TAHUN 2014 DALAM TATA KELOLA PEMERINTAHAN DI KELURAHAN DURI BARAT - Zulfian, Rahmat Ade; Jumili Arianto; Indra Primahardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by political changes in Indonesia, which are followed by increasing issues of decentralization and democratization. The research is directed at evaluating the implementation of Good Governance in Duri Barat Subdistrict, with the aim of explaining field conditions, analyzing government governance, and identifying the influence of Good Governance principles on government governance. This research is quantitative research that uses a statistical approach to analyze the observed symptoms. Conducted in Duri Barat Subdistrict, Duri City, Riau Province, from March to April 2023. The population of this research was all government employees in Duri Barat Subdistrict, with sampling using total sampling because the population was less than 100. The data collected consisted of data primary through questionnaires and interviews. The research instrument includes Good Governance and government governance variables. The data analysis techniques used include simple linear regression analysis, t test, and coefficient of determination test to determine the influence of the independent variable on the dependent variable. Based on the data obtained from 14 employees which were then processed and tested, conclusions can be drawn from the overall results of the test results analysis. Simple linear regression explains that for every additional percentage of Good Governance, government governance increases positively.